2016
DOI: 10.1111/bcp.13173
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, controlled, multicentre clinical trial of the antipyretic effect of intravenous paracetamol in patients admitted to hospital with infection

Abstract: AimNo randomized study has been conducted to investigate the use of intravenous paracetamol (acetaminophen, APAP) for the management of fever due to infection. The present study evaluated a new ready‐made infusion of paracetamol.MethodsEighty patients with a body temperature onset ≥38.5°C in the previous 24 h due to infection were randomized to a single administration of placebo (n = 39) or 1 g paracetamol (n = 41), and their temperature was recorded at standard intervals. Rescue medication with 1 g paracetamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…APAP is a widely used and effective antipyretic and analgesic drug. Unfortunately, APAP overdose is the leading cause of acute liver injury or even liver failure . Thus, the treatment for APAP-induced hepatotoxicity is highly desired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APAP is a widely used and effective antipyretic and analgesic drug. Unfortunately, APAP overdose is the leading cause of acute liver injury or even liver failure . Thus, the treatment for APAP-induced hepatotoxicity is highly desired.…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen ( N -acetyl- p -aminophenol, APAP), a widespread and effective analgesic and antipyretic drug, can cause severe liver injury or even acute liver failure when it is used with acute or cumulative overdose . In the United States, around 30000 people every year are subjected to APAP hepatotoxicity .…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen trials (19 comparisons) with a total of 2415 participants reported on serious adverse events. The included trials assessed the effects of five different fever therapy interventions: ibuprofen versus placebo (three trials), 47 48 49 paracetamol versus placebo (six trials), 50 51 52 53 54 55 physical cooling versus no intervention (three trials), 56 57 58 antipyretics plus physical cooling versus no intervention (two trials), 18 59 and physical cooling plus antipyretics versus antipyretics (two trials). 60 61 All 2415 participants were admitted to hospital; 2050 were critically ill, and 251 were non-critically ill (supplementary table S1).…”
Section: Resultsmentioning
confidence: 99%
“…We collected data of patient demographics, LOS, medical history, and comorbidities including history of drug resistance, surgical history, and current infection information including culture results, CURB-65 (confusion of new onset, blood urea nitrogen greater than 7 mmol/L or 19 mg/dL, respiratory rate of 30 breaths per minute or greater, systolic blood pressure less than 90 mmHg or diastolic blood pressure 60 mmHg or less, and age of 65 or older) score, antibiotics used including macrolides, chronic intake of statins, current medication intake, CRP level, erythrocyte sedimentation rate, white blood cell differentials, liver function tests when available, and temperature. Temperature normalization was recorded, defined as temperature 37.1 C. 11…”
Section: Data Collection Processmentioning
confidence: 99%